PLANEJAMENTO ESTRATÉGICO EM MICRO E PEQUENAS EMPRESAS (MPEs): Estudo de Caso numa Empresa do Comércio Varejista de Itanhaém e Região - COTTA, CELSO PEIXOTO (2018)
The search for better results has motivated organizations to develop their strategic capacity to face the changes and challenges in the context of the globalized economy. In this way, in search of success in the business world, companies have overcome several challenges, and for this they use varied strategies. In the retail sector, there is a very intense transformation process, and these changes are causing organizations to seek to improve their work environment by modifying their practices, looking for differentials to overcome the barriers of the market. It is necessary to prepare the company, in the face of opportunities and threats, to optimize the competitive advantages over the competition. Planning is contrary to improvising. Whoever improvises does not always get results. In the meantime, strategic planning for an organization is perennial, but for this the company must think strategically, and this is represented and managed by managers and entrepreneurs who, in turn, should be prepared to produce and lead this tool to meet the challenges of competitiveness, increasing the possibility of obtaining a good position in the market in which it operates. This study has as its central focus analyze the strategic planning in a micro-enterprise of the retail of hydraulic and electrical materials in the city of Itanhaém located on the coast of São Paulo’s state. From the research carried out, it was possible to reach the proposed objective and demonstrating that the importance of strategic planning for micro-enterprises. At the end of the study, it was possible to verify that the results presented by Idralar as a small-sized business that has been active for 23 years in the local commerce with a consolidated image in its market are in agreement with what is presented in other similar studies, with strategic planning not being carried out by the company formally, despite perceiving it in the manager’s speeches, with its elements being considered by them in the day-to-day of their business, being verified in this case success factors that can be attributed to the specialization in a commerce segment, to the commitment, loyalty and commitment of partners and employees to better serve their clients. Results showed that the SME studied uses informal, short-term strategic planning, according to its necessities, as it depends on financial return in order to plan new investments, believing technical knowledge is enough for the longevity of the company.